2019
DOI: 10.33094/26410249.2019.14.87.96
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Home, Clutter, and Place Attachment Predicting Life Satisfaction among Women of Color: Home is Beyond Physical Space

Abstract: We examined psychological home, place attachment, clutter, and life satisfaction with adult women of color (n = 99; M age = 50.33 years old) drawn from a larger national sample of women who self-identified with clutter tendencies. We assessed resource (i.e., annual household income, homeownership status, and relationship status) and contextual (i.e., type of dwelling, number of people in household, and years in residence) variables, plus measures of psychological home, place attachment, and clutter, as predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…2015;Wojnicka and Pustułka 2019). Studies on psychological home among natives have reported that gender is an important factor in understanding the importance of self-identity in one's home (Crum and Ferrari. 2019a).…”
Section: Gender Studies On the Meaning Of Homementioning
confidence: 99%
See 1 more Smart Citation
“…2015;Wojnicka and Pustułka 2019). Studies on psychological home among natives have reported that gender is an important factor in understanding the importance of self-identity in one's home (Crum and Ferrari. 2019a).…”
Section: Gender Studies On the Meaning Of Homementioning
confidence: 99%
“…2020). Psychological home is a significant predictor of life satisfaction (Crum and Ferrari. 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Vand der Klis and Karsten [ 1 ] identify three frameworks to understand the concept of home, namely the physical dwelling itself, activities surrounding the dwelling, and particular social settings that are familiar to the person around their dwelling area. Literature from a variety of fields indicated that the concept of home frequently was associated with feelings of safety and security within the individuals that partake within the concept [ 2 ] however when the experience of home is burdened by over-abundance of clutter, this feeling may result in a lower sense of well-being [ 3 ]. Such associations highlight the importance of the home concept as a construct worth studying for community psychologists who are predominantly interested in how living environments impacts the well-being of individuals and communities [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological home has been consistently associated with life satisfaction in both Italy [ 9 ] and America [ 2 , 3 , 10 ]. For instance, using data gathered in Italy, psychological home predicted resilience in both migrant and non-migrant populations [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent investigations explored whether an overabundance of possessions, termed clutter, had a negative influence on one's well-being (e.g., Roster et al, 2016). For instance, Crum and Ferrari (2019a) analyzed whether clutter impacted overall life satisfaction among women of color. Results showed that life satisfaction was higher among women with less clutter.…”
mentioning
confidence: 99%